From Data to Decisions: The Role of Business Intelligence in Developing Effective Marketing Strategies - Pardede, Adinda Jennifer (Business Management, 2025)
This article aims to explain the role of BI in developing effective marketing strategies. This article will discuss how BI can be used to analyze markets, identify potential target markets, develop products and services that suit customer needs, optimize pricing strategies, increase the effectiveness of promotions and advertising, and better manage customer relationships. Apart from that, this article will also analyze the application of BI in various marketing case studies. The scope of this article covers various aspects of BI relevant to marketing, including the definition and main components of BI, the ETL (Extract, Transform, Load) process, BI tools and technologies, data-driven market analysis, data-driven product and service development, optimizing pricing strategies with BI, increasing the effectiveness of promotions and advertising with BI, and BI in customer relationship management (CRM). The result of this research is that by using BI, marketers can collect and analyze data from various sources, such as sales transaction data, demographic data, online behavior data, and customer feedback data. This information can be used to identify different market segments, develop products and services tailored to market needs, set optimal prices, plan more effective promotional campaigns, and better manage customer relationships.